2013
DOI: 10.1039/c3lc50403d
|View full text |Cite
|
Sign up to set email alerts
|

An innovative sample-to-answer polymer lab-on-a-chip with on-chip reservoirs for the POCT of thyroid stimulating hormone (TSH)

Abstract: A new sample-to-answer polymer lab-on-a-chip, which can perform immunoassay with minimum user intervention through on-chip reservoirs for reagents and single-channel assay system, has been designed, developed and successfully characterized as a point-of-care testing (POCT) cartridge for the detection of thyroid stimulating hormone (TSH). Test results were obtained within 30 minutes after a sample was dropped into the POCT cartridge. The analyzed results of TSH showed a linear range of up to 55 μIU mL(-1) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Studies with aptamers in lateral flow devices and disposable biosensors have demonstrated the stability and reliability of the assay with whole blood or patient serum 26 55 56 57 . The POCT set-up generally needs to be easy to handle, simple to manipulate and capable of rapid data processing in a single device, even when used by an untrained personnel 57 58 59 60 . The developed assay platform provides a simple and rapid method for detecting LCN2 in a serial order.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with aptamers in lateral flow devices and disposable biosensors have demonstrated the stability and reliability of the assay with whole blood or patient serum 26 55 56 57 . The POCT set-up generally needs to be easy to handle, simple to manipulate and capable of rapid data processing in a single device, even when used by an untrained personnel 57 58 59 60 . The developed assay platform provides a simple and rapid method for detecting LCN2 in a serial order.…”
Section: Discussionmentioning
confidence: 99%
“…2.6). A sample-to-answer immunoassay chip, for example, can be continuously replicated for the detection of thyroid-stimulating hormone [102]. However, with mechanical milling, it is not easy to obtain complex, three-dimensional high aspect ratio structures at the micrometric scale.…”
Section: Direct Machiningmentioning
confidence: 99%
“…Image of the milled aluminum master using CNC milling machine and c the replicated polymeric device for the sample-to-answer immunoassay chip [102] Duarte et al were able to integrate dynamic, solid-phase DNA extraction and PCR amplification steps using a PT device [105]. Starting with two separate polyester films, both printed with toner layers and laser cut with microfluidic channels, they then sandwiched and laminated these layers with base and cover polyester films that were manufactured with holes to provide access to laser-cut channels.…”
Section: Fig 26 a Bmentioning
confidence: 99%
“…The merging of microarrays with microfluidics has also been the subject of intensive research [13] due to significant advantages associated with reducing manual operations and expensive reagent consumption, as well as allowing much more rapid detection [14][15][16].…”
Section: Introductionmentioning
confidence: 99%